Quo Vadis: Mentoring in Entrepreneurship Education? - Yuliawati, Livia (Jurnal Entrepreneur dan Entrepreneurship, 2013)
Nowadays the rise of mentoring concept has entered to entrepreneurship domain. Rela-tionship between mentee and mentor, which has been applied into career and organizational con-text, also is being tried into entrepreneurship education as the relationship between new entrepre-neurs and experienced entrepreneurs. Since entrepreneurship is believed as the answer for unem-ployment, poverty, and economic crisis, then entrepreneurial success tend to be measured only byeconomic criteria. Many entrepreneurship educations were designing various projects to equip newentrepreneurs in order to create new venture. It also influences how mentors help the mentees,which also emphasize to gain profits, revenue growth, and sustainability. This paradigm seems toignore psychological characteristic of entrepreneurs and to narrow entrepreneurship as the pursuitof money. This article will review where the direction of mentoring in entrepreneurship education,what roles of mentor, and expected learning outcomes from mentoring in entrepreneurship educa-tion.